Climate change: Epistemological integration - Franciskovic Ingunza, Millitza (2018)
Knowledge in general has entered a new phase of its development, we have an immense power that allows us to obtain the sequence of the genes of any living being that walks, flies or swims; But today, however, we face the problem of how to integrate all this information so that everyone can understand and use it. The great challenge we face is knowing how we convert data, information into knowledge and this will only be possible through the exchange of information between different disciplines of knowledge and this task will only be completed if we are able to communicate this knowledge to The public opinion in general because all this knowledge will affect our lives very deeply in the future of the coming years.This article is framed in this context and the discipline called environmental law is oriented to the understanding and explanation of the phenomenon of climate change and its consequent impact on the environment, so we will integrate it, for a better and effective understanding, with the Disciplines of the natural sciences. That is, what the author of the complex thought, in his opportunity, of the urgent necessity to appeal to the interdisciplinarity, to establish conceptual indications; As is the case at hand: climate change. It will develop and explain the thinking of a renowned scientist who in the last century was considered the propeller of human ecology.